The Effect of Chin-Cap Treatment On the Vertical Dimensions of the Face and on the Facial Profile in Subjects With Skeletal Class 3 Anterior Cross-Bite - Oktay Üner; Sema Ilgar; Neslihan Karabekir (Galenos Yayinevi, 1988)
The Effect of Chin-Cap Treatment On the Vertical Dimensions of the Face and on the Facial Profile in Subjects With Skeletal Class 3 Anterior Cross-Bite This Study was carried out for the purpose of investigating the effects of chin-cap treatment on the vertical dimension of the face and profile in subjects having skeletal Class 3 relationship with anterior cross-bite. The control group consists of 12 individuals having an average chronological age of 10 years 2 months where the research group consists of 16 individuals having an average chronological ages of 9 years 2 months. Two lateral cephalometric films were taken from each of these individuals at the beginning and at the end of the research. After having taken the first cephalometric films, of the research group individuals, chin-cap with 600 gr. total force from tip of chin and directed to the mandibular condyle making an angle of 35-40 degrees with the individual's occlusal plane and a posterior occlusal bite plane were applied. Chin-cap was carried by the research group averaging 14 hours per day for a period of one year and at the end of this period the second lateral cephalometric films were taken. It is observed that the use of chin-cap has the effect of increasing ANB, FMA and Y-axis angles. Besides, it causes the protrusion of upper and lower lips and retrusion and inclination of lower incisors.